2009
DOI: 10.1074/jbc.m109.017624
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Synthetic Adaptors and Substrates for Controlled ClpXP Degradation

Abstract: Facile control of targeted intracellular protein degradation has many potential uses in basic science and biotechnology. One promising approach to this goal is to redesign adaptor proteins, which can regulate proteolytic specificity by tethering substrates to energy-dependent AAA؉ proteases. Using the ClpXP protease, we have probed the minimal biochemical functions required for adaptor function by designing and characterizing variant substrates, adaptors, and ClpX enzymes. We find that substrate tethering medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The scaffolding adaptor SspB adaptor uses the NTD ClpX as a simple tethering site (Dougan et al, 2003; Bolon et al, 2004; Park et al, 2007; Davis et al, 2009). As shown schematically in Figure 3 (box), if CpdR-dependent degradation also uses the NTD ClpX in a similar manner, it should be possible to bypass the need for the NTD ClpX by artificially tethering CpdR to ΔN-ClpX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffolding adaptor SspB adaptor uses the NTD ClpX as a simple tethering site (Dougan et al, 2003; Bolon et al, 2004; Park et al, 2007; Davis et al, 2009). As shown schematically in Figure 3 (box), if CpdR-dependent degradation also uses the NTD ClpX in a similar manner, it should be possible to bypass the need for the NTD ClpX by artificially tethering CpdR to ΔN-ClpX.…”
Section: Resultsmentioning
confidence: 99%
“…However, if the NTD ClpX serves as more than a passive anchor, simply tethering CpdR would not restore PdeA degradation. We adopted a previously reported tethering system where human FKBP12 protein is fused to E. coli ΔN-ClpX, and F KBP12- r apamycin- b inding (FRB) domain of the rat mTOR protein is fused to E. coli SspB (Davis et al, 2009). Addition of rapamycin induces dimerization of FKBP12 and FRB, tethering SspB to the ΔN-ClpX fusion so adaptor function no longer requires NTD ClpX (Davis et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Hence the weaker K m would result in faster degradation, since the unfolding of native protein is a ratelimiting step for protein degradation by ClpX (Kenniston et al, 2003). The strong interaction of GtYjbH and Spx could increase the effective concentration of Spx to the pore of ClpX, and then the equilibrium would shift towards the generation of degraded products (Davis et al, 2009). Finally, a model mechanism is proposed of how GtYjbH is an adaptor mediating Spx proteolysis by ClpXP.…”
Section: Discussionmentioning
confidence: 99%
“…A solution to this problem is to specifically target the encoded gene product for conditional depletion (29). In doing so, the gene remains in its natural context, and the encoded product functions normally at the appropriate dose prior to its removal.Prior studies have demonstrated the utility of this approach for specific cases by reengineering target proteins such that they contain a peptide degradation signal that is recognized by a processive protease (7,15,20,24,29,53). In early examples, a degradation peptide that has a weakened affinity for the protease was selected, and then an adapter protein that increases the effective local concentration of the target near the protease to increase degradation was conditionally expressed (20,29).…”
mentioning
confidence: 99%